Impact of Abdominal Obesity on Thyroid Auto-Antibody Positivity: Abdominal Obesity Can Enhance the Risk of Thyroid Autoimmunity in Men. (13th March 2020) - Zynat, Jazyra; Li, Suli; Ma, Yanrong; Han, Li; Ma, Fuhui; Zhang, Yuyuan; Xing, Bei; Wang, Xinling; Guo, Yanying
Abstract : Background . The interrelation between obesity and autoimmune thyroid diseases is complex and has not been confirmed. The aim of the present study was to observe the relationship between thyroid autoimmunity and obesity, especially abdominal obesity, in a large population. Methods . A total of 2253 residents who had lived in Xinjiang for more than 3 years were enrolled. Serum thyroid hormone concentration, thyroid autoantibodies, lipid parameters, Weight, height, and waist and hip circumference were measured. Results . The prevalence of thyroid peroxidase antibody (TPOAb) and/or thyroglobulin antibody (TgAb) positive was 32.1% (21.2% in men and 37% in women, P < 0.01 ). Compared with women, men had significantly higher TG levels, waist circumference, and hip circumference levels (P < 0.01 ), while women showed higher TSH, TPOAb, and TgAb levels (P < 0.01 ). The prevalence of overweight and obesity was 71.1% in men and 63.5% in women. Men had a higher prevalence of abdominal obesity than women (56.6% in men and 47.6% in women, P < 0.01 ). TPOAb correlates positively with waist circumference ( r = 0.100, P < 0.05 ) in men. Binary logistic analysis showed that TPOAb positivity had increased risks of abdominal obesity in men, and the OR was 1.1044 (95% CI 1.035, 1.151, P < 0.05 ). Conclusion . Our results indicate that men had higher lipid levels, thicker waist circumference, and higher prevalence of overweight, obesity, and abdominal obesity. Abdominal obesity is a risk factor for TPOAb positivity in men, suggesting that abdominal obesity can enhance the risk of thyroid autoimmunity in men.